2010
DOI: 10.1371/journal.pone.0014433
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Treatment of Painful HIV-Associated Sensory Neuropathy: A Systematic Review and Meta-Analysis of Randomised Controlled Trials

Abstract: BackgroundSignificant pain from HIV-associated sensory neuropathy (HIV-SN) affects ∼40% of HIV infected individuals treated with antiretroviral therapy (ART). The prevalence of HIV-SN has increased despite the more widespread use of ART. With the global HIV prevalence estimated at 33 million, and with infected individuals gaining increased access to ART, painful HIV-SN represents a large and expanding world health problem. There is an urgent need to develop effective pain management strategies for this conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
151
1
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(159 citation statements)
references
References 66 publications
(97 reference statements)
1
151
1
6
Order By: Relevance
“…13,14 Added to these challenges, which are not necessarily unique to South Africa, is the high rate of HIV in this country and the paucity of evidence for treating painful HIV-related neuropathy. 15 Clinical practice guidelines for management of neuropathic pain: expert panel recommendations for South Africa S Chetty, E Baalbergen, A I Bhigjee, P Kamerman, J Ouma, R Raath, M Raff, S Salduker…”
mentioning
confidence: 99%
“…13,14 Added to these challenges, which are not necessarily unique to South Africa, is the high rate of HIV in this country and the paucity of evidence for treating painful HIV-related neuropathy. 15 Clinical practice guidelines for management of neuropathic pain: expert panel recommendations for South Africa S Chetty, E Baalbergen, A I Bhigjee, P Kamerman, J Ouma, R Raath, M Raff, S Salduker…”
mentioning
confidence: 99%
“…Importantly, improving our understanding of SN pathogenesis may lead to effective preventative strategies, or even pathogenesis-based treatments for a condition that currently lacks effective analgesic options. 8 Of the individual SNPs associated with neuropathy, allele 2 was associated with reduced risk in each case (Table 1). The FV18_ext1 haplotype was associated with increased risk of HIV-SN.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 While not fatal, HIV-SN has a significant negative impact on psychological, social and economic well-being 4 and there are no proven treatments for the pain. 8 The pathogenesis of HIV-SN has not been fully explained, but human [9][10][11] and animal studies 12 indicate that inflammation plays a central role. Genetic studies support an inflammatory etiology, providing evidence of associations with polymorphisms in TNFA, IL4 and IL10.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis found that smoked cannabis was significantly more effective than placebo in providing pain relief to patients with HIV-related neuropathy, while the efficacy of more commonly prescribed drugs, such as gabapentin and pregabalin, did not differ significantly from placebo. 11 Concerns regarding the prescribing of medical cannabis have also been expressed on the basis of a perceived lack of information related to its mechanism of action. Applying this model more generally, it could be argued that physicians should be discouraged from prescribing a host of routine pharmacological treatments, including gabapentin and pregabalin, whose mechanisms of action are still largely unclear.…”
mentioning
confidence: 99%